1998
DOI: 10.1046/j.1432-1327.1998.2560570.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the hydrophobicity gradient of an amphipathic peptide to its mode of association with lipids

Abstract: A class of peptides that associate with lipids, known as oblique-orientated peptides, was recently described [Brasseur R., Pillot, T., Lins, L., Vandekerckhove, J. & Rosseneu, M. (1997) Trends Biochem. Sci. 22, 167Ϫ171]. Due to an asymmetric distribution of hydrophobic residues along the axis of the Ahelix, such peptides adopt an oblique orientation which can destabilise membranes or lipid cores. Variants of these oblique peptides, designed to have an homogeneous distribution of hydrophobic and hydrophilic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…bicity gradients appear to promote membrane destabilization by causing the peptide to partially penetrate the bilayer (4,7,29). In our series, the peptides with the steepest hydrophobicity gradients, SMAP29 and CAP18, also had the most potent antimicrobial activity (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…bicity gradients appear to promote membrane destabilization by causing the peptide to partially penetrate the bilayer (4,7,29). In our series, the peptides with the steepest hydrophobicity gradients, SMAP29 and CAP18, also had the most potent antimicrobial activity (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…Tilted peptides have been identified in many proteins and protein fragments interacting with lipids such as viral fusion proteins (14), signal peptides of membrane-translocated proteins (15), and proteins involved in lipid metabolism (16). In the latter, they may increase the accessibility of enzymes to hydrophobic substrates (12,17,18). Hence, in contrast with classical amphipathic helices currently found in proteins and supported to promote protein stability, tilted peptides are a signature for instability (13).…”
mentioning
confidence: 99%
“…The 25 to 35 fragment (AIGLAWIPYFG) shows a hydrophobicity profile similar to that of the SIV tilted peptide, well known for its fusogenic properties (22, 26), although, as shown on Fig. 1, the two stretches have no sequence identity.The three-dimensional structure of the 25 to 35 Ebola virus peptide was calculated as previously described, assuming a helical secondary structure (3,6,7,28). Small peptides can adopt ␣ and ␤ type structures (12,22,33).…”
mentioning
confidence: 99%
“…It was shown that the ability of the Ebola virus peptide to induce lipid destabilization correlates with an ␣-helical structure, in the absence of Ca 2ϩ (33). Furthermore, the fusogenic activity of the tilted fragments of apolipoprotein A-II and SIV fusion protein increases with the helical content (22,28), stressing the importance of the helix structure for lipid destabilizing capacities. Moreover, nuclear magnetic resonance studies have indicated that the fragments of the fusogenic domain of GP41 and of HA2, which correspond to tilted peptides in terms of hydrophobic/hydrophilic properties, are predominantly ␣-helical in a lipid-like environment (15,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation